Response time and muscle activation patterns of the upper limbs during different strikes in kendo - Yotani, K.; Tamaki, H.; Kirimoto, H.; Yuki, A.; Kitada, K.; Maesaka, S.; Ogita, F. (Archives of Budo, 2013)
ackground and Study Aim: Kendo is an example of a decision-making sport and involves rapidly alternating defensive and offensive movements of a shinai (bamboo sword). The aim of this study was response time and muscle activation patterns during two types of kendo strikes. Material and Methods: Kendo athletes (n=7), other athletes (n=7), and sedentary participants (n=7) performed 10 "Men" strikes (target height, 1.65 m) and 10 "Kote" strikes (target height, 1.15 m). Muscle activity of the bilateral biceps brachii, bilateral triceps brachii, and right flexor carpi ulnaris muscles was recorded using electromyography (EMG). Results: The kendo and other athletes had similar response times and shorter response times than the sedentary participants. The kendo athletes exhibited different timing of muscle activation onset between the two tasks, whereas the other athletes and sedentary participants exhibited no differences in timing. The EMG magnitude differed between kendo athletes and non-kendo subjects (other athletes and sedentary participants). Conclusions: In decision-making sports, differences in neuromuscular control, but not in response times, are associated with athletic experience.